Microtask Crowdsourcing Platform for Inclusive Digital Governance - Sri Hariani Eko Wulandari; Rozlina Binti Mohamed; Nurzeti Aqtar Binti Ahmad Azuan; Edvan Perdana Sandjaya (MDP Student Conference, 2026)
Digital governance increasingly relies on data-driven, platform-based architectures to coordinate interactions among government organizations, citizens, and economic actors. In this study, governance activities refer to operational public service tasks in Bank Jatim’s aid distribution, including beneficiary data verification, MSME eligibility validation, transaction reporting, confirmation based QRCODE, and monitoring, which are decomposed into independent microtasks. Although such platforms improve efficiency and administrative control, participation often remains structurally uneven, favoring actors with higher digital capacity and organizational resources. This study investigates how microtask crowdsourcing can be designed as a socio-technical mechanism to enhance inclusive digital governance without compromising accountability or execution quality. Using a Design Science Research methodology, a web-based microtask crowdsourcing platform was designed, implemented, and evaluated. Inclusiveness was operationalized through participation breadth, task accessibility, and contribution continuity. Evaluation involved functional testing, usability assessment using the System Usability Scale, and comparative analysis of participation outcomes before and after implementation empirically.